The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.buildenv.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Internal insulation applied in heritage multi-storey buildings with wooden beams embedded in solid masonry brick façades

Abstract: Internal insulation is investigated in a building with a wooden beam construction and masonry brick walls. Measurements were carried out and used to validate a hygrothermal simulation. The risk of mould growth in the wooden beams and in the interface between the insulation and the brick wall was evaluated.A solution with a 200mm area without insulation above and below the floor/ceiling was investigated. At low rain exposure coefficients (Catch Ratio, CR≤0.1) and with a wall orientation towards the west, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Results from the VTT model suggests no wood decay in the beam end for neither the un-hydrophobized Walls 2 and 5 nor the hydrophobized Walls 3 and 6. The presented results are supported by the findings from other studies [3,23] investigating the performance of solid masonry walls fitted with the internal insulation in combination with deliberate thermal bridge near the floor partition. This indicates worse conditions in the beam ends due to the internal floor-to-ceiling insulation, while a deliberate thermal bridge above, or above and below the floor partition reduces the increase in RH caused by the internal insulation.…”
Section: The Embedded Wooden Beam Endssupporting
confidence: 89%
“…Results from the VTT model suggests no wood decay in the beam end for neither the un-hydrophobized Walls 2 and 5 nor the hydrophobized Walls 3 and 6. The presented results are supported by the findings from other studies [3,23] investigating the performance of solid masonry walls fitted with the internal insulation in combination with deliberate thermal bridge near the floor partition. This indicates worse conditions in the beam ends due to the internal floor-to-ceiling insulation, while a deliberate thermal bridge above, or above and below the floor partition reduces the increase in RH caused by the internal insulation.…”
Section: The Embedded Wooden Beam Endssupporting
confidence: 89%
“…The basic characteristics of the used brick types can be found in Table 3 and Figure 3, which clearly show the variations in the bricks' moisture properties. When evaluating the hygrothermal performance of a massive masonry wall, one is typically interested in frost damage at the exterior surface, decay of embedded wooden floors and mould growth on the interior surface [3,[25][26][27]. The latter is mainly important in the case of thermal bridges and of less importance in 1D simulations.…”
Section: Hygrothermal Simulation Objectmentioning
confidence: 99%
“…Calcium silicate proved the best performance in regard to moisture performance, however calcium silicate also has the highest thermal conductivity. Harrestrup et al [22] monitored a case of internal insulation of 40mm aerowolle on a heritage brick building, and the effect of intentional thermal bridges above and below supportive wooden beams. They found that leaving a 200mm uninsulated gap above and below the beams yielded a lower risk of mould growth, however this was found to be very dependent on the orientation and the thickness of the existing wall.…”
Section: Accepted M M a N U mentioning
confidence: 99%